2022
DOI: 10.3390/plants12010171
|View full text |Cite
|
Sign up to set email alerts
|

Population Genomics Study and Implications for the Conservation of Zabelia tyaihyonii Based on Genotyping-By-Sequencing

Abstract: Zabelia tyaihyonii (Nakai) Hisauti and H. Hara is a perennial shrub endemic to Republic of Korea that grows naturally in only a very limited region of the dolomite areas of Gangwon-do and Chungcheongbuk-do Provinces in the Republic of Korea. Given its geographical characteristics, it is more vulnerable than more widely distributed species. Despite the need for comprehensive information to support conservation, population genetic information for this species is very scarce. In this study, we analyzed the geneti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 70 publications
0
5
0
Order By: Relevance
“…We also suggest a more in‐depth future analysis of the demographic history of our focal species' five genetic units by sampling more individuals and populations. The challenges to be expected, however, as also for other rare and/or endangered Korean endemics (e.g., Kang et al., 2023; Yun & Oh, 2022), are the little‐known information about the past regional geological and temporal events that may have impacted the present population size and structure of the species (i.e., historical bottlenecks). The effective population sizes of the genetic subdivisions reported here, therefore, should be viewed with caution because possible demographic events that may have occurred after their divergence (e.g., bottleneck and/or expansion) were not taken into account.…”
Section: Discussionmentioning
confidence: 99%
“…We also suggest a more in‐depth future analysis of the demographic history of our focal species' five genetic units by sampling more individuals and populations. The challenges to be expected, however, as also for other rare and/or endangered Korean endemics (e.g., Kang et al., 2023; Yun & Oh, 2022), are the little‐known information about the past regional geological and temporal events that may have impacted the present population size and structure of the species (i.e., historical bottlenecks). The effective population sizes of the genetic subdivisions reported here, therefore, should be viewed with caution because possible demographic events that may have occurred after their divergence (e.g., bottleneck and/or expansion) were not taken into account.…”
Section: Discussionmentioning
confidence: 99%
“…Despite this, the CJ_S6 population does not show unique genetic characteristics and instead forms a clade with geographically more distant populations within CLI, indicating genetic homogeneity. Because a previous study conducted by Kang et al ( 2023 ) had limited coverage of CLII populations, it is challenging to directly compare their findings with our current study. The study demonstrated significant genetic divergence for the CJ_S6 population within the CLI populations.…”
Section: Discussionmentioning
confidence: 83%
“…There is no evidence that Z. mosanensis has been found anywhere other than in Z. tyaihyonii's habitats. Consequently, Z. mosanensis is regarded as a synonym of Z. tyaihyonii (Sun, 1999), that view is well maintained among Korean researchers (Chae et al, 2023;Kang et al, 2023;Won & Kim, 2007).…”
Section: Study Species and Population Samplingmentioning
confidence: 97%
See 2 more Smart Citations